The Effects of Storage Age of Blood in Massively Transfused Burn Patients: A Secondary Analysis of the Randomized Transfusion Requirement in Burn Care Evaluation Study. Issue 12 (December 2018) - Cartotto, Robert; Taylor, Sandra L.; Holmes, James H.; Peck, Michael; Cochran, Amalia; King, Booker T.; Bhavsar, Daval; Tredget, Edward E.; Mozingo, David; Greenhalgh, David; Pollock, Brad H.; Palmieri, Tina L.
Abstract : Objectives: Major trials examining storage age of blood transfused to critically ill patients administered relatively few blood transfusions. We sought to determine if the storage age of blood affects outcomes when very large amounts of blood are transfused. Design: A secondary analysis of the multicenter randomized Transfusion Requirement in Burn Care Evaluation study which compared restrictive and liberal transfusion strategies. Setting: Eighteen tertiary-care burn centers. Patients: Transfusion Requirement in Burn Care Evaluation evaluated 345 adults with burns greater than or equal to 20% of the body surface area. We included only the 303 patients that received blood transfusions. Interventions: The storage ages of all transfused red cell units were collected during Transfusion Requirement in Burn Care Evaluation. A priori measures of storage age were the the mean storage age of all transfused blood and the proportion of all transfused blood considered very old (stored ≥ 35 d). Measurements and Main Results: The primary outcome was the severity of multiple organ dysfunction. Secondary outcomes included time to wound healing, the duration of mechanical ventilation, and in-hospital mortality. There were 6, 786 red cell transfusions with a mean (± SD) storage age of 25.6 ± 10.2 days. Participants received a mean of 23.4 ± 31.2 blood transfusions (range, 1–219) and a mean of 5.3 ± 10.7 units of very old blood. Neither mean storage age nor proportion of very old blood had any influence on multiple organ dysfunction severity, time to wound healing, or mortality. Duration of ventilation was significantly predicted by both mean blood storage age and the proportion of very old blood, but this was of questionable clinical relevance given extreme variability in duration of ventilation (adjusted r 2 ⩽ 0.01). Conclusions: Despite massive blood transfusion, including very old blood, the duration of red cell storage did not influence outcome in burn patients. Provision of the oldest blood first by Blood Banks is rational, even for massive transfusion. Abstract : Supplemental Digital Content is available in the text.